Sistem Administrasi Kepegawaian Terhadap Kepuasan Pegawai Pada Kementerian Pupr Balai Wilayah Sungai Sumatera II Medan - Inri Monika Helena Purba; Cut Fitri Rostina (CERED Indonesia Institute, 2022)
This study aims to identify the personnel administration system on employee satisfaction at the Sumatra II River Basin Center, Medan. The survey approach used in this survey uses a qualitative approach that combines observation, literature study, interviews, and documentation. Those who become resource persons to obtain information and become pioneers in order to facilitate the administrative system are civil servants in the staffing section. The results showed that 20% of 100% were dissatisfied with the use of the administrative system because of the knowledge and age factors that had an impact on the use of the personnel administration system application on the satisfaction of the employees of the Medan Sungai Sumatera II Regional Office and 80% of 100% indicated that the employees were satisfied with the personnel administration system.